2021
DOI: 10.1021/acs.chemmater.1c02426
|View full text |Cite
|
Sign up to set email alerts
|

Precise Control of Noncovalent Interactions in Semiconducting Polymers for High-Performance Organic Field-Effect Transistors

Abstract: Performed through side-chain engineering or by incorporating intramolecular locking units, the directionality and dynamic nature of noncovalent interactions are particularly attractive for the design of novel semiconducting materials in a wide variety of applications. This work investigates the nature and position of hydrogen bonding (intra- versus intermolecular), with the objective of developing a rational approach to the design of new semiconducting materials with improved properties in the solid state. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 56 publications
0
41
0
Order By: Relevance
“…The polar carbonyl group in the DPP core enables the molecule to form intramolecular hydrogen bonds, which tune the backbone planarity and the frontier molecular orbital energy levels. [80][81][82] The noncovalent hydrogen bond interactions in the DPP building blocks are different depending on the flanking heterocycles. For example, if the DPP core is flanked by six-membered-ring phenyl groups, the repulsion between the lactam oxygen and the phenyl α-hydrogen causes a twist in the structure.…”
Section: Noncovalent Hydrogen Bonds In Diketopyrrolopyrrole-based Con...mentioning
confidence: 99%
See 1 more Smart Citation
“…The polar carbonyl group in the DPP core enables the molecule to form intramolecular hydrogen bonds, which tune the backbone planarity and the frontier molecular orbital energy levels. [80][81][82] The noncovalent hydrogen bond interactions in the DPP building blocks are different depending on the flanking heterocycles. For example, if the DPP core is flanked by six-membered-ring phenyl groups, the repulsion between the lactam oxygen and the phenyl α-hydrogen causes a twist in the structure.…”
Section: Noncovalent Hydrogen Bonds In Diketopyrrolopyrrole-based Con...mentioning
confidence: 99%
“…The polar carbonyl group in the DPP core enables the molecule to form intramolecular hydrogen bonds, which tune the backbone planarity and the frontier molecular orbital energy levels. [ 80–82 ]…”
Section: Semiconducting Polymers With Hydrogen Bondingmentioning
confidence: 99%
“…Then, underlining the strong impact in the hydrogen bonding units incorporated into conjugated polymer, intramolecular conformational locks can be established resulting in increased backbone planarity, enhanced -delocalization and field-effect mobility ( h FET ). [19][20][21][22] This elegant strategy also brings out new properties and functions, one of which is the self-healing ability (Fig. 1b).…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, it was revealed that the incorporation of hydrogen bonding moieties among these novel conjugated polymer designs is particularly effective in tailoring the mechanical deformability and maintaining or even boosting the charge transport values in TFTs. [19][20][21][22] Interestingly, the combination of dynamic H-bonds into organic semiconductors has brought out new property and function such as self-healing ability which will be explained in the Section 3. [23][24][25] 2.2.1 Block copolymer approach.…”
Section: Conjugated Polymer Engineeringmentioning
confidence: 99%
“…The incorporation of fluorine atoms can be advantageous since it can potentially allow for strain dissipation upon stress through non-covalent H-F bonds. 35,36 On the other ends, fluorination can result in the p-conjugated backbone to become more planar, thus increasing crystallinity and the rigidity of the macromolecule.…”
Section: Introductionmentioning
confidence: 99%